Identifikasi dan Fotodegradasi Pigmen Klorofil Rumput Laut Caulerpa racemosa (Forsskal) J.Agardh - Lisiard Dimara; Helena Tuririday; Tien N.B. Yenusi (Jurnal Biologi Papua, 2012)
Identification of chlorophyll compound of Caulerpa racemosa has been carried out using Thin Layer Chromatography (TLC) method. Four compound has been found namely xanthophll, chlorophyll b, chlorophyll a, and phaeophytin. Xanthophyll was identified with the yellow spot on TLC plates which the Rf is 0,46. Chlorophyll b is yellow green spot with Rf is 0,61, the Rf of Chlorophyll a is 0,69 with the color is blue green, whereas phaeophytin is indicated as a black spot with the Rf  0,77. Volpi and UV light sources were used in this study, the volpi light radiation was caused chlorophyll extract degradation about 80,87% at Qy of l 663 nm, and the UV light source caused 72,27%  degradation at l 663 nm.Key words: identification, photodegradation, chlorophyll, Caulerpa racemosa.